Regularized threshold iteration method for impulsive noise suppression in underwater acoustic communication - Nana LI; Youming LI; Mingchen YU; Qianqian LU (Dianxin kexue)
Impulsive noise interference can seriously affect the performance of underwater acoustic communication systems.An impulsive noise suppression method based on regularized threshold iteration was presented.Firstly,the null subcarrier matrix was used to separate impulsive noise from Gaussian white noise and useful signals.Then,based on the theory of compressed sensing,the impulsive noise estimation problem was transformed into a regularization problem by introducing a threshold iteration,and the impulsive noise was estimated by using a threshold function to obtain the estimated value of the impulsive noise.Finally,the estimated impulsive noise was subtracted from the received signal.The simulation results show that the proposed method can effectively reduce the bit error rate (BER) and mean square error (MSE),and improve the reliability of signal transmission in underwater acoustic communication environment.